SISTEM PENYIRAMAN TANAMAN OTOMATIS BERBASIS INTERNET OF THINGS DAN ARDUINO SERTA MONITORING DENGAN TELEGRAM - Rico Amanda (bit-Tech, 2024)
Watering plants is very important if plants are to grow healthy and fertile. Many plant owners do not water their plants because they are busy at work and busy activities outside the home. Watering plants in the form of a system that can work automatically is an integrated design that can help human work. The aim of this research is the application of the Internet of Things and Telegram in watering plants, as well as creating an application for monitoring plant growth and care using the Telegram application. The method used in this research is the internet of things. Internet of Things is a concept where certain objects have the ability to transfer data via a WiFi network, so this process does not require human-to-human or human-to-computer interaction. Everything is run automatically with the program. The Internet of Things is usually called LoT and this technology has developed rapidly starting from wireless technology, micro-electromechanical systems (MEMS) and the internet. The results of this research are that by using an automatic plant watering system based on the internet of things, plants can remain well maintained and the development of the plants can also be monitored via telegram. The results of the questionnaire respondents' answers were on average above 50% in choosing the answer "Strongly Agree". These results show that this application is easy to use and meets user needs.